2018
DOI: 10.1186/s13023-018-0815-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Bradykinin-mediated angioedema: a systematic investigation of epidemiological studies

Abstract: BackgroundBradykinin-mediated angioedema (Bk-AE) can be life-threatening and requires specific targeted therapies. Knowledge of its epidemiology may help optimize its management.MethodsWe systematically searched the medical literature to identify abstracts of interest indexed between 1948 and March, 2016. We used published national survey data on the proportion of the population treated with angiotensin-converting enzyme inhibitors (ACEI) to derive estimates of the population prevalence of ACEI-AE in the USA, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
2
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(100 citation statements)
references
References 35 publications
2
84
2
12
Order By: Relevance
“…The highest prevalence was noted in Sweden (1.56 patients per 100,000 inhabitants), followed by Italy and Norway with confirmed prevalence rates of 1.51 per 100,000 and 1.50 per 100,000 respectively . A recent comparison of national prevalence rates for C1‐INH‐HAE revealed that the epidemiology of this condition is stable; its prevalence was about 1.50 per 100.000 across the six European countries that were compared . Accurate estimates of the prevalence of C1‐INH‐HAE in a given population are hindered by the rare occurrence of the disease, poor awareness of the condition, the absence of established registries, the small number of studies on the prevalence and epidemiology of HAE, and diverse methods of data collection (registries, data from patient organizations or surveys).…”
Section: Discussionmentioning
confidence: 99%
“…The highest prevalence was noted in Sweden (1.56 patients per 100,000 inhabitants), followed by Italy and Norway with confirmed prevalence rates of 1.51 per 100,000 and 1.50 per 100,000 respectively . A recent comparison of national prevalence rates for C1‐INH‐HAE revealed that the epidemiology of this condition is stable; its prevalence was about 1.50 per 100.000 across the six European countries that were compared . Accurate estimates of the prevalence of C1‐INH‐HAE in a given population are hindered by the rare occurrence of the disease, poor awareness of the condition, the absence of established registries, the small number of studies on the prevalence and epidemiology of HAE, and diverse methods of data collection (registries, data from patient organizations or surveys).…”
Section: Discussionmentioning
confidence: 99%
“…Die Häufi gkeit von HAE-Attacken kann von wenigen bis zu mehr als 100 pro Jahr variieren [ 6,7 ] . Die in der Literatur geschätzte Prävalenz der Krankheit reicht von 1 : 10.000 bis 1 : 150.000 [8][9][10] . HAE betrifft alle ethnischen Gruppen [ 11 ] .…”
Section: Resultsunclassified
“…A systematic investigation of epidemiological studies found an estimated prevalence of ACEi AE between 0.7 and 1.7 per 10,000 inhabitants in the USA and between 1.0 and 2.6 per 10,000 inhabitants in Germany [3]. The weighted incidence of AE due to ACE inhibitor treatment was 0.3% in a large meta-analysis of randomized trials [4].…”
Section: Introductionmentioning
confidence: 99%